Clinical success of IUI cycles with donor sperm is not affected by total inseminated volume: a RCT. Issue 2 (15th February 2018) - Rodriguez-Purata, Jorge; Latre, Laura; Ballester, Marta; González-Llagostera, Clara; Rodríguez, Ignacio; Gonzalez-Foruria, Iñaki; Buxaderas, Rosario; Martinez, Francisca; Barri, Pedro N; Coroleu, Buenaventura
Abstract: STUDY QUESTION: What is the impact on live birth rates (LBR) when a donor IUI (dIUI) cycle is performed with an insemination volume of 0.5 mL versus the usual 0.2 mL? SUMMARY ANSWER: LBR after a dIUI cycle is no different when performed with 0.5 versus 0.2 mL. WHAT IS ALREADY KNOWN: An IUI has an important role in the treatment of severe male infertility, and is often used in same-sex female couples and single parents. Different variables have been studied to determine factors correlated with clinical outcomes (IUI scheduling, ovarian stimulation, sperm parameters) but little is known about the inseminated volume. The use of conical bottom test tubes could contribute substantially to the loss of inseminated spermatozoa because it precludes the total recovery of the sample. Additionally, the insemination catheter could uphold this reduction causing sperm adhesion on the inner walls of the insemination catheter, decreasing even more the total inseminated volume. It is expected that utilizing an IUI approach that increases sperm volume in the fallopian tubes (0.5 mL rather than 0.2 mL) at the time of ovulation will lead to higher LBRs. To avoid bias related to sperm quality, the study population was restricted to dIUI cycles. STUDY DESIGN, SIZE, AND DURATION: A parallel-group, double-blinded, RCT, including patients undergoing natural or stimulated dIUI, was performed between March 2013 and April 2015. dIUI cycles ( n = 293) were randomized through a computer-generated list to undergo insemination with 0.2 mL (control group) or 0.5 mL (study group), of which 24 were excluded (protocol deviation) and 269 received the allocated intervention. Patients with the presence of tubal factor infertility, grades III–IV endometriosis, >3 previous dIUI cycles or with ≥3 follicles >14 mm were excluded. The study was designed with 80% power to detect a 5% difference in LBR with a reference of 15% and a two-tailed 5% significance level. The required sample size was 118 per group. PARTICIPANTS/MATERIALS, SETTING AND METHOD: There were 143 cycles (0.2 mL group) and 126 cycles (0.5 mL group). The primary end-point of the trial was LBR per dIUI cycle in both treatment groups. Clinical pregnancy rate and miscarriage rate were evaluated as secondary outcomes. MAIN RESULTS AND THE ROLE OF CHANCE: No adverse events were reported during the study trial. Study groups (0.2 versus 0.5 mL, respectively) were similar in age (35.8 ± 3.9 versus 35.4 ± 4.0 years: mean±SD), and had similar anti-Mullerian hormone levels (2.2 ± 1.8 versus 2.0 ± 1.5 ng/mL), basal antral follicle count (13.2 ± 6.4 versus 13.6 ± 6.0), BMI (23.5 ± 3.9 versus 23.7 ± 4.1 kg/m 2 ), number of follicles >17 mm (1.1 ± 0.5 versus 1.1 ± 0.5), total gonadotrophin dose (553.1 ± 366.3 versus 494.6 ± 237.1 IU), and total motile sperm count (8.22 ± 7.1 versus 7.7 ± 5.7 million). Similar clinical pregnancy rates (18.9% (27/143) versus 19.8% (25/126), NS), LBRs (15.4% (22/143) versus 19.0% (24/126), NS) and miscarriage rates (18.5% (5/27) versus 4.0% (1/25), NS) were observed between groups. LIMITATIONS REASONS FOR CAUTION: The study was not powered to detect differences in the secondary outcomes, clinical pregnancy and miscarriage rates. The randomization was performed at the dIUI cycle level, therefore, the results are reported as success rate per dIUI cycle rather than per patient. WIDER IMPLICATIONS OF THE FINDINGS: This is the first RCT to show that the inseminated volume is not correlated with the probability of a live birth. The miscarriage rate was higher in the 0.2 mL group, although this difference was not statistically significant. If the lower miscarriage rate observed in the 0.5 mL group is confirmed, this could be related to the presence of uterine contractions similar of those generated during sexual intercourse, which may be implicated in the inception of early biochemical embryo–endometrium communication. STUDY FUNDING/COMPETING INTERESTS: All authors declare having no conflict of interest with regard to this trial. No funding was received for this study. This research was performed under the auspices of 'Càtedra d'Investigació en Obstetrícia I Ginecologia' of the Department of Obstetrics, Gynaecology and Reproductive Medicine, Hospital Universitari Quiron-Dexeus, Universitat Autònoma de Barcelona. TRIAL REGISTRATION NUMBER: The trial was registered at clinicaltrials.gov (Identifier: NCT03006523).